Improving older adults' accessibility to the web using real-time online interactive guides. Issue 164 (August 2022) - Taieb-Maimon, Meirav; Vaisman-Fairstein, Elior
Highlights: GoldNet- guides the user step-by-step when performing online operations A user study was conducted on 30 novice older adults attending a daycare center GoldNet was effective as a human tutor and significantly better than video guidance GoldNet accelerated the learning process, providing visual cues and instructions Learning was faster for the younger age group and most of it resulted from practice Abstract: Internet use by older adults is increasing and has the potential to improve their mental and social wellbeing, however it is still low compared to other age groups for various online activities. The objective of this study was to develop and evaluate a computerized expert system, GoldNet, which functions as a human expert and guides the user, step-by-step and in real time, when performing online operations. A user study was conducted on 30 older adults (over 65 years old) that attend an adult daycare center. The participants were all novice users with no prior experience using the Internet. A stratified randomized between participants experimental design was used to evaluate users' performance and satisfaction before and after receiving guidance, after practice, and after a two-week period without controlled practice. Participants were assigned to one of three study groups according to the guidance they received: GoldNet guides, video guidance, or guidance from a personal human tutor. During the experiment participants' eye movements were monitored. The results indicate that by using GoldNet's automated guides, older adults can perform online tasks with high effectiveness, efficiency, and user satisfaction, performing comparably to users trained by a personal human tutor and significantly better than users relying on video guidance. GoldNet was also found beneficial as a refresher tool after a period without controlled training.